The control of melanogenesis in early avian embryos - Hulley, Philippa Anne (Department of Molecular and Cell Biology, 2024)
The developing neural crest in avian embryos presents a unique system for the investigation of cell migration and differentiation. A variety of histological, cellular and molecular techniques have been used in this study to explore and clarify the exact sequence of events occurring during the determination and differentiation of neural crest cells into melanocytes, to discover where in the developing embryo these events take place and to investigate the mechanisms whereby these processes are controlled. Homo- and heterotypic combinations of white (Yhite Plymouth Rock x Cornish Game) and black (Black Australorp x New Hampshire Red) chick epidermis and dermis have been used to demonstrate that premelanocytes migrate first through the sub-epidermal mesenchyme and then begin to cross into the epidermis from day 4. Results from these grafts and from tritium-labelling studies strongly suggest that there is little or no reverse migration from epidermis to dermis. This resolves the conflict of whether premelanocytes migrate immediately into the epidermis from the neural crest or spread out laterally around the body in the dermis before crossing into the epidermis. Since the microenvironment is thought to play a key role in the control of neural crest cell diversification, the timing and route of migration may be critical factors in melanocyte differentiation. Pigmented melanocytes first become visible in the dermis at day 5 and tyrosinase activity (the key enzyme in melanin production) was detected in 5 day chick skin using a radiometric assay. In sicu vi hybridization of sections through 5 day embryos using Digoxygenin-labelled riboprobe revealed the presence of numerous tyrosinase mRNA-positive cells in the dermis and crossing into the epidermis. It is therefore likely that the dermis provides the first appropriate environment for melanocyte differentiation and not the epidermis as previously thought. However the role of the dermis may be permissive rather than active because when the dermis was replaced with gut mesenchyme, melanocytes still differentiated. The presence of epidermis was shown to be critical for melanocyte differentiation. When 4 day dermis (prior to the appearance of melanin) was 1 cultured in isolation from epidermis, melanocytes did not difrerentiate. Similarly, when epidermis was replaced with gut or chorionic epithelium, melanocytes largely failed to differentiate. Therefore the epidermis seems to be inducing terminal melanocyte differentiation, albeit at a distance from the migrating cells. Although the dermis does not seem to be essential for melanocyte differentiation, it appears to inhibit melanocyte differentiation in white pattern feathers. When the epidermis on the dorsal surface of quail wing buds was replaced with epidermis from a white chick, normally pigmented feathers formed but when the ventral wing epidermis was replaced, most of the resulting feathers were unpigmented. This is the normal colour pattern of quail wing feathers and the result therefore indicates that the ventral wing dermis is responsible for inhibiting melanocyte differentiation in the white pattern feathers of an otherwise pigmented bird. The question of how melanocytes locate and physically migrate into the epidermis was addressed by developing a variety of novel organ culture procedures. When whole 4 day skin or heterotypic combinations of pigmented dermis with white epidermis were cultured on rafts floating in medium containing GRGDS, the cellbinding site peptide sequence of fibronectin, epidermal pigmentation was severely inhibited. When the laminin cell-binding site peptide, YIGSR, was similarly vii used, normally pigmented epidermis and feathers developed. Therefore it is likely that melanocytes use fibronectin and not laminin when migrating through the dermis and into the epidermis . Melanocytes may also need to produce proteases in order to invade the epidermis since raft culture of skin in TLCK, a serine protease inhibitor, prevented epidermal melanisation. Finally, the ability of the epidermis to chemotactically attract melanocytes was investigated by assessing the change in distribution of melanocytes in dermis cultured on a filter above a well containing pieces of epidermis. The epidermis appears to be producing a diffusible factor which attracts melanocytes and is not mimicked by NGF, EGF, bFGF or retinoic acid. This is the first evidence that the epidermis may play a role in the homing of melanocytes.The developing neural crest in avian embryos presents a unique system for the investigation of cell migration and differentiation. A variety of histological, cellular and molecular techniques have been used in this study to explore and clarify the exact sequence of events occurring during the determination and differentiation of neural crest cells into melanocytes, to discover where in the developing embryo these events take place and to investigate the mechanisms whereby these processes are controlled. Homo- and heterotypic combinations of white (Yhite Plymouth Rock x Cornish Game) and black (Black Australorp x New Hampshire Red) chick epidermis and dermis have been used to demonstrate that premelanocytes migrate first through the sub-epidermal mesenchyme and then begin to cross into the epidermis from day 4. Results from these grafts and from tritium-labelling studies strongly suggest that there is little or no reverse migration from epidermis to dermis. This resolves the conflict of whether premelanocytes migrate immediately into the epidermis from the neural crest or spread out laterally around the body in the dermis before crossing into the epidermis. Since the microenvironment is thought to play a key role in the control of neural crest cell diversification, the timing and route of migration may be critical factors in melanocyte differentiation. Pigmented melanocytes first become visible in the dermis at day 5 and tyrosinase activity (the key enzyme in melanin production) was detected in 5 day chick skin using a radiometric assay. In sicu vi hybridization of sections through 5 day embryos using Digoxygenin-labelled riboprobe revealed the presence of numerous tyrosinase mRNA-positive cells in the dermis and crossing into the epidermis. It is therefore likely that the dermis provides the first appropriate environment for melanocyte differentiation and not the epidermis as previously thought. However the role of the dermis may be permissive rather than active because when the dermis was replaced with gut mesenchyme, melanocytes still differentiated. The presence of epidermis was shown to be critical for melanocyte differentiation. When 4 day dermis (prior to the appearance of melanin) was 1 cultured in isolation from epidermis, melanocytes did not difrerentiate. Similarly, when epidermis was replaced with gut or chorionic epithelium, melanocytes largely failed to differentiate. Therefore the epidermis seems to be inducing terminal melanocyte differentiation, albeit at a distance from the migrating cells. Although the dermis does not seem to be essential for melanocyte differentiation, it appears to inhibit melanocyte differentiation in white pattern feathers. When the epidermis on the dorsal surface of quail wing buds was replaced with epidermis from a white chick, normally pigmented feathers formed but when the ventral wing epidermis was replaced, most of the resulting feathers were unpigmented. This is the normal colour pattern of quail wing feathers and the result therefore indicates that the ventral wing dermis is responsible for inhibiting melanocyte differentiation in the white pattern feathers of an otherwise pigmented bird. The question of how melanocytes locate and physically migrate into the epidermis was addressed by developing a variety of novel organ culture procedures. When whole 4 day skin or heterotypic combinations of pigmented dermis with white epidermis were cultured on rafts floating in medium containing GRGDS, the cellbinding site peptide sequence of fibronectin, epidermal pigmentation was severely inhibited. When the laminin cell-binding site peptide, YIGSR, was similarly vii used, normally pigmented epidermis and feathers developed. Therefore it is likely that melanocytes use fibronectin and not laminin when migrating through the dermis and into the epidermis . Melanocytes may also need to produce proteases in order to invade the epidermis since raft culture of skin in TLCK, a serine protease inhibitor, prevented epidermal melanisation. Finally, the ability of the epidermis to chemotactically attract melanocytes was investigated by assessing the change in distribution of melanocytes in dermis cultured on a filter above a well containing pieces of epidermis. The epidermis appears to be producing a diffusible factor which attracts melanocytes and is not mimicked by NGF, EGF, bFGF or retinoic acid. This is the first evidence that the epidermis may play a role in the homing of melanocytes.